2008
DOI: 10.1121/1.2821955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social, demographical and behavioral factors on the sound level evaluation in urban open spaces

Abstract: The aim of this study is to analyze the effects of social, demographical and behavioral factors as well as long-term sound experience on the subjective evaluation of sound level in urban open public spaces. This is based on a series of large scale surveys in 19 urban open spaces in Europe and China. The results suggest that the effects of social/demographical factors, including age, gender, occupation, education and residential status, on the sound level evaluation are generally insignificant, although occupat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 21 publications
4
55
1
5
Order By: Relevance
“…Dubois found that soundscape evaluation is influenced not only by sound intensity but also by a variety of human factors [11]. Yu and Kang propose that, within urban open spaces, some of an individual's social, demographic, and behavioural factors affect his or her evaluation of sound levels [12]. Cain et al found that two independent emotional dimensions of a soundscape related to its "Calmness" and "Vibrancy" [13].…”
Section: Introductionmentioning
confidence: 99%
“…Dubois found that soundscape evaluation is influenced not only by sound intensity but also by a variety of human factors [11]. Yu and Kang propose that, within urban open spaces, some of an individual's social, demographic, and behavioural factors affect his or her evaluation of sound levels [12]. Cain et al found that two independent emotional dimensions of a soundscape related to its "Calmness" and "Vibrancy" [13].…”
Section: Introductionmentioning
confidence: 99%
“…Differences at societal and cultural levels influence the perception of sonic environments [3][4][5]. A large survey [6] found that some socio-economic factors, notably occupation and education, were more strongly associated with the perceived sound level than factors such as age, gender, or residential status. At the level of the individual, psychological differences can be charted in terms of broadly defined personality dimensions [7][8][9][10] or narrowly defined traits, such as noise sensitivity [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Judgments of a soundscape can depend upon the specific location and its visual appearance [7], the type of activity or activities that occur there [8], the observer's personal history and expectations, emotional content and culture [9] and age [4]. How can this multiplicity of factors be evaluated in a useful way so that decisions about soundscape improvement or preservation can be made?…”
Section: Soundscape Definedmentioning
confidence: 99%